Effect of low fluoride acidic dentifrices on dental remineralization - Brighenti, Fernanda Lourenção [UNESP]; Takeshita, Eliana Mitsue [UNESP]; Sant'ana, Camila de Oliveira [UNESP]; Buzalaf, Marília Afonso Rabelo; Delbem, Alberto Carlos Botazzo [UNESP] (FapUNIFESP (SciELO), 2013)
This study evaluated the capacity of fluoride acidic dentifrices (pH 4.5) to promote enamel remineralization using a pH cycling model, comparing them with a standard dentifrice (1,100 μgF/g). Enamel blocks had their surface polished and surface hardness determined (SH). Next, they were submitted to subsurface enamel demineralization and to postdemineralization surface hardness analysis. The blocks were divided into 6 experimental groups (n=10): placebo (without F, pH 4.5, negative control), 275, 412, 550, 1,100 μgF/g and a standard dentifrice (positive control). The blocks were submitted to pH cycling for 6 days and treatment with dentifrice slurries twice a day. After pH cycling, surface and crosssectional hardness were assessed to obtain the percentage of surface hardness recovery (%SHR) and the integrated loss of subsurface hardness (δKHN). The results showed that %SHR was similar among acidic dentifrices with 412, 550, 1,100 μgF/g and to the positive control (Tukey's test; p>0.05). For ΔKHN, the acidic dentifrice with 550 μg F/g showed a better performance when compared with the positive control. It can be concluded that acidic dentifrice 550 μgF/g had similar remineralization capacity to that of positive control.
Keywords: Dental caries; Dental enamel; Dentifrices; Fluoride; Tooth remineralization